Aggregate interface reinforced high-performance concrete

By pretreating the aggregate surface and using aggregate interface reinforcement, the problem of the concrete interface transition zone is solved, significantly improving the mechanical properties and durability of concrete, and achieving higher compressive, tensile strength and permeability .

CN119285300APending Publication Date: 2025-01-10SHANGHAI CONSTR BUILDING MATERIALS TECH GRP CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411411889.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

There are pores, microcracks and uneven chemical composition in the interface transition area between the aggregate and the cement slurry in concrete, which affects the mechanical properties and durability of the concrete.

Method used

By pretreating the surface of the crude aggregate, using silane coupling agents, nano-silica and other aggregate interface reinforcers, combined with optimizing the concrete mix ratio, the interface bond strength between the aggregate and the cement slurry is significantly improved, and the improvement of the improvement of the interface bonding strength between the aggregate and the cement slurry is improved. Interface chemical composition and microstructure.

Benefits of technology

It significantly improves the compressive strength, tensile strength and flexural strength of concrete, reduces permeability and porosity, enhances the permeability and durability, reduces the use of gelled materials, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005078230790000101
    Figure BDA0005078230790000101
Patent Text Reader

Abstract

The invention discloses aggregate interface reinforced high-performance concrete, which is prepared from the following ingredients in parts by weight: 300 to 400 parts of cement, 50 to 100 parts of coal ash, 50 to 100 parts of slag powder, 600 to 800 parts of fine aggregate, 1000 to 1200 parts of pretreated coarse aggregate, 5 to 10 parts of water reducing agents, 150 to 180 parts of water and 10 to 20 parts of aggregate interface reinforcing agents. The aggregate interface enhancer comprises a silane coupling agent, nano silicon dioxide, ethanol and water; the aggregate interface enhancer comprises the following components in parts by weight: 3-5 parts of a silane coupling agent, 3-5 parts of nano silicon dioxide, 10-15 parts of ethanol and 5-10 parts of water; the pretreated coarse aggregate is 5-25mm continuous graded broken stone, the surface of the pretreated coarse aggregate contains an aggregate interface enhancer, and the silt content of the pretreated coarse aggregate is not more than 1.0%. By pretreating the surface of the coarse aggregate and optimizing the mixing ratio of the concrete, the interface bonding strength between the aggregate and the cement paste is remarkably improved, the mechanical property and durability of the concrete are improved, and the preparation quality of the concrete is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and in particular relates to high-performance concrete with aggregate interface reinforcement. Background Art

[0002] As one of the most widely used building materials, the performance of concrete directly affects the quality and durability of buildings. In concrete, the interfacial transition zone (ITZ) between aggregate and cement paste is the weak link in concrete. There are often pores, microcracks and uneven chemical composition at the interface with cement paste, which can easily cause cracking and damage of concrete, and have an important impact on the mechanical properties and durability of concrete. In order to improve the weak interfacial transition zone, improve the macroscopic properties of concrete, and enhance the durability of concrete, mineral admixtures such as mineral powder and fly ash are often used to improve the interfacial transition zone and pore structure, increase the degree of hydration and structural density.

[0003] If the aggregate interface is pretreated to enhance the interface, more cementitious materials can be saved. Common methods for enhancing the aggregate interface include physical, chemical, high-temperature autoclaving and microwave heating. Therefore, choosing the appropriate pretreatment method plays an important role in improving the performance of concrete. At the same time, the pretreatment method reduces the processing flow of aggregates in the later stage and improves the production efficiency of concrete. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art. The present invention provides a high-performance concrete with reinforced aggregate interface. The present invention significantly improves the interface bonding strength between aggregate and cement paste, improves the mechanical properties and durability of concrete, and improves the quality of concrete preparation by pretreating the surface of coarse aggregate and optimizing the concrete mix ratio.

[0005] In order to achieve the above invention purpose, the technical solution provided by the present invention is as follows:

[0006] A high-performance concrete with aggregate interface reinforcement, which comprises the following components by weight: 300-400 parts of cement, 50-100 parts of fly ash, 50-100 parts of slag powder, 600-800 parts of fine aggregate, 1000-1200 parts of pretreated coarse aggregate, 5-10 parts of water reducing agent, 150-180 parts of water, and 10-20 parts of aggregate interface reinforcement agent;

[0007] The aggregate interface strengthener comprises a silane coupling agent, nano-silicon dioxide, ethanol and water; the aggregate interface strengthener comprises the following components by weight: 3-5 parts of silane coupling agent, 3-5 parts of nano-silicon dioxide, 10-15 parts of ethanol and 5-10 parts of water;

[0008] The pre-treated coarse aggregate is 5-25 mm continuously graded crushed stone, the surface of the pre-treated coarse aggregate contains an aggregate interface strengthener, and the mud content of the pre-treated coarse aggregate is not more than 1.0%.

[0009] Furthermore, the fine aggregate is medium sand with a fineness modulus of 2.3-2.8, and the mud content of the fine aggregate is not more than 2.0%.

[0010] Furthermore, the cement is silicate cement or ordinary silicate cement, and the strength grade of the cement is not less than 42.5.

[0011] Furthermore, the fly ash is Grade I fly ash, and the ignition loss of the fly ash is not more than 5%; the slag powder is Grade S95 slag powder, and the specific surface area of ​​the slag powder is not less than 400m 2 / kg.

[0012] Furthermore, the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate of the water reducing agent is not less than 25%.

[0013] Furthermore, the silane coupling agent is one of epoxy silane coupling agents, amino silane coupling agents, and methacrylate silane coupling agents, or a mixture of more than one of these.

[0014] Furthermore, the specific steps of preparing the aggregate interface strengthener are:

[0015] S1, weighing ethanol and water according to weight components, adding them into a reaction kettle and stirring them evenly to obtain a mixed solvent A;

[0016] S2, adding a weighed silane coupling agent to the mixed solvent under continuous stirring, and stirring for 30-60 minutes to obtain a mixed solvent B;

[0017] S3, adding the weighed nano-silicon dioxide into the reaction kettle and stirring for 60-90 minutes to make the nano-silicon dioxide evenly dispersed in the solvent to obtain a mixed solvent C;

[0018] S4, performing ultrasonic dispersion on the obtained mixed solvent C, the ultrasonic time is 15 minutes, and obtaining an aggregate interface strengthener.

[0019] Furthermore, the specific steps of the coarse aggregate pretreatment are:

[0020] The first step is to use a crusher to preliminarily crush the sand and gravel aggregates, screen and separate the aggregates in different particle size ranges, and select the aggregates in the particle size range of 5-25mm;

[0021] The second step is to place the selected aggregate in a flushing tank for flushing, and then air-dry the aggregate after the flushing is completed;

[0022] The third step is to immerse the air-dried aggregate in the prepared aggregate interface strengthener, and use a vacuum impregnation machine to absorb the aggregate interface strengthener for 30-60 minutes;

[0023] The fourth step is to dry the aggregate after the vacuum impregnation machine has finished adsorption, thus completing the pretreatment of the coarse aggregate.

[0024] Furthermore, the vacuum impregnation machine is used in an environment with a temperature of 20-30° C. and a pressure of 0.6-0.8 MPa.

[0025] Based on the above technical solution, the high-performance concrete with aggregate interface reinforcement in the present invention has achieved the following technical effects through practical application:

[0026] 1. The high-performance concrete with aggregate interface reinforcement of the present invention significantly improves the interface bonding strength between aggregate and cement paste, improves the mechanical properties and durability of concrete, and improves the quality of concrete preparation by pretreating the surface of coarse aggregate and optimizing the concrete mix ratio.

[0027] 2. The high-performance concrete with aggregate interface reinforcement of the present invention uses an aggregate interface reinforcement agent to treat the aggregate surface, thereby increasing the viscosity with the cement paste, enhancing the aggregate slurry coating ability, improving the interface chemical composition and microstructure between the aggregate and the cement paste, increasing the interface bonding strength, reducing pores and microcracks, reducing the permeability of the concrete, and enhancing the anti-seepage ability; thereby significantly improving the compressive strength, tensile strength and flexural strength of the concrete.

[0028] 3. The high-performance concrete with aggregate interface reinforcement of the present invention strengthens the bonding force between aggregate and cement-based paste by causing the silicon groups attached to the surface of the aggregate to undergo hydrolysis reaction to form silanol, which reacts with the hydroxyl groups on the surface of the cement-based paste to form hydrogen bonds or covalent bonds; nano-silicon dioxide can promote crystal nucleation and crystal growth in the cement-based paste, improve the interface transition zone, reduce the total porosity and critical porosity, and can synergistically complement with the silane coupling agent, be distributed at the interface of the cement to form a cross-linked structure, and strengthen the integrity of the concrete.

[0029] 4. The high-performance concrete with aggregate interface reinforcement of the present invention uses vacuum impregnation to replace traditional multiple surface spraying or coating, which reduces the operation process on the one hand and avoids the problems of uneven spraying on the aggregate surface or the interface reinforcement agent on the aggregate surface being washed away during mixing, resulting in poor effect. The interface reinforcement agent is adsorbed in the pores on the surface of the aggregate, ensuring that sufficient interface reinforcement agent can react with the concrete slurry.

[0030] 5. The high-performance concrete with aggregate interface reinforcement of the present invention can reduce the amount of cement to a certain extent, save costs, and reduce the environmental impact of cement production by adding appropriate amounts of fly ash and slag powder into the concrete. At the same time, it has good working performance, durability and crack resistance, is easy to construct, and can meet the needs of various complex projects. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical scheme and effect of the present invention clearer, the present invention is described below by specific examples. However, it should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0032] A high-performance concrete with aggregate interface reinforcement, which comprises the following components by weight: 300-400 parts of cement, 50-100 parts of fly ash, 50-100 parts of slag powder, 600-800 parts of fine aggregate, 1000-1200 parts of pretreated coarse aggregate, 5-10 parts of water reducing agent, 150-180 parts of water, and 10-20 parts of aggregate interface reinforcement agent;

[0033] The aggregate interface strengthener comprises a silane coupling agent, nano-silicon dioxide, ethanol and water; the aggregate interface strengthener comprises the following components by weight: 3-5 parts of silane coupling agent, 3-5 parts of nano-silicon dioxide, 10-15 parts of ethanol and 5-10 parts of water;

[0034] The silicon groups attached to the surface of the aggregate undergo hydrolysis to form silanols, which react with the hydroxyl groups on the surface of the cement paste to form hydrogen bonds or covalent bonds, thereby strengthening the bonding force between the aggregate and the cement paste. Nano-silicon dioxide can promote crystal nucleation and crystal growth in the cement paste, improve the interface transition zone, reduce the total porosity and critical porosity, and can cooperate with silane coupling agents to form a cross-linked structure at the interface of the cement paste, thereby strengthening the integrity of the concrete.

[0035] The pre-treated coarse aggregate is 5-25 mm continuously graded crushed stone, the surface of the pre-treated coarse aggregate contains an aggregate interface strengthener, and the mud content of the pre-treated coarse aggregate is not more than 1.0%.

[0036] The fine aggregate is medium sand with a fineness modulus of 2.3-2.8, and the mud content of the fine aggregate is not more than 2.0%.

[0037] The cement is silicate cement or ordinary silicate cement, and the strength grade of the cement is not less than 42.5.

[0038] The fly ash is Grade I fly ash, and the ignition loss of the fly ash is not more than 5%; the slag powder is Grade S95 slag powder, and the specific surface area of ​​the slag powder is not less than 400m2 / kg.

[0039] The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate of the water reducing agent is not less than 25%.

[0040] The silane coupling agent is one of epoxy silane coupling agents, amino silane coupling agents, and methacrylate silane coupling agents, or a mixture of more than one of these.

[0041] The specific steps of preparing the aggregate interface strengthener are:

[0042] S1, weighing ethanol and water according to weight components, adding them into a reaction kettle and stirring them evenly to obtain a mixed solvent A;

[0043] S2, adding a weighed silane coupling agent to the mixed solvent under continuous stirring, and stirring for 30-60 minutes to obtain a mixed solvent B;

[0044] S3, adding the weighed nano-silicon dioxide into the reaction kettle and stirring for 60-90 minutes to make the nano-silicon dioxide evenly dispersed in the solvent to obtain a mixed solvent C;

[0045] S4, performing ultrasonic dispersion on the obtained mixed solvent C, the ultrasonic time is 15 minutes, and obtaining an aggregate interface strengthener.

[0046] The specific steps of the coarse aggregate pretreatment are:

[0047] The first step is to use a crusher to preliminarily crush the sand and gravel aggregates, screen and separate the aggregates in different particle size ranges, and select the aggregates in the particle size range of 5-25mm;

[0048] The second step is to place the selected aggregate in a flushing tank for flushing, and then air-dry the aggregate after the flushing is completed;

[0049] The third step is to immerse the air-dried aggregate in the prepared aggregate interface strengthener, and use a vacuum impregnation machine to absorb the aggregate interface strengthener for 30-60 minutes;

[0050] The fourth step is to dry the aggregate after the vacuum impregnation machine has finished adsorption, thus completing the pretreatment of the coarse aggregate.

[0051] The vacuum impregnation machine is used at an ambient temperature of 20-30° C. and a pressure of 0.6-0.8 MPa.

[0052] By using aggregate interface strengthener to treat the aggregate surface, the viscosity with cement paste is increased, the aggregate coating ability is enhanced, the interface chemical composition and microstructure between aggregate and cement paste are improved, the interface bonding strength is improved, the pores and microcracks are reduced, the permeability of concrete is reduced, and the anti-seepage ability is enhanced; thereby significantly improving the compressive strength, tensile strength and flexural strength of concrete.

[0053] The specific preparation process of a high-performance concrete with aggregate interface reinforcement is as follows:

[0054] S1, dry mix cement, fly ash and mineral powder for 30 seconds, then add water and admixtures and stir for 1 minute;

[0055] S2, adding the pretreated coarse aggregate and fine aggregate into the mixed slurry, and obtaining a high-performance concrete with aggregate interface reinforcement after mixing for 3 minutes.

[0056] Example 1

[0057] A high-performance concrete with aggregate interface reinforcement comprises the following components: 320 parts of cement, 60 parts of fly ash, 50 parts of slag powder, 700 parts of fine aggregate, 1100 parts of pretreated coarse aggregate, 7 parts of water reducing agent, 150 parts of water and 14 parts of aggregate interface reinforcement agent.

[0058] The preparation process of the aggregate interface strengthener is as follows: add 12 parts of ethanol and 8 parts of water into a reactor and stir evenly to form a mixed solvent; under stirring, slowly add 3 parts of aminosilane coupling agent into the mixed solvent and continue stirring for 40 minutes to fully mix and hydrolyze it; gradually add 5 parts of nano-silica into the reactor and continue stirring for 60 minutes to ensure that the nano-silica is evenly dispersed in the solution; ultrasonically disperse for 15 minutes to obtain a uniform and stable aggregate interface strengthener, which is sealed and stored for later use.

[0059] The preparation process of pretreated aggregate is as follows:

[0060] 1) After using a crusher to initially crush the sand and gravel aggregates, the aggregates of different particle size ranges are initially screened and separated; coarse aggregates of 5-25 mm are selected for subsequent processes;

[0061] 2) Install a stirring device in the water tank or increase the disturbance of the water flow to ensure the uniformity of the aggregate after being rinsed in the flushing tank, and then air-dry;

[0062] 3) Immerse the aggregate in the aggregate interface strengthener, with the liquid level of the aggregate interface strengthener just covering the top of the aggregate; use a vacuum impregnation machine to adsorb the interface strengthener for 40 minutes at 25°C and 0.6 MPa;

[0063] 4) After the aggregate is dried, the required pretreated aggregate is obtained.

[0064] Example 2

[0065] A high-performance concrete with aggregate interface reinforcement comprises the following components: 330 parts of cement, 70 parts of fly ash, 60 parts of slag powder, 700 parts of fine aggregate, 1000 parts of pretreated coarse aggregate, 8 parts of water reducing agent, 160 parts of water and 14 parts of aggregate interface reinforcement agent.

[0066] The preparation process of the aggregate interface strengthener is as follows: add 13 parts of ethanol and 7 parts of water into a reactor and stir evenly to form a mixed solvent; under stirring, slowly add 4 parts of aminosilane coupling agent into the mixed solvent and continue stirring for 40 minutes to fully mix and hydrolyze it; gradually add 3 parts of nano-silica into the reactor and continue stirring for 60 minutes to ensure that the nano-silica is evenly dispersed in the solution; ultrasonically disperse for 15 minutes to obtain a uniform and stable aggregate interface strengthener, which is sealed and stored for later use.

[0067] The preparation process of pretreated aggregate is as follows:

[0068] 1) After using a crusher to initially crush the sand and gravel aggregates, the aggregates of different particle size ranges are initially screened and separated;

[0069] 2) Install a stirring device in the water tank or increase the disturbance of the water flow to ensure the uniformity of the aggregate after being rinsed in the flushing tank, and then air-dry;

[0070] 3) Immerse the aggregate in the aggregate interface strengthener, with the liquid level of the aggregate interface strengthener just covering the top of the aggregate; use a vacuum impregnation machine to adsorb the interface strengthener for 50 minutes at 25°C and 0.8 MPa;

[0071] 4) After the aggregate is dried, the required pretreated aggregate is obtained.

[0072] Comparative Example 1

[0073] A high-performance concrete with aggregate interface reinforcement comprises the following components: 330 parts of cement, 70 parts of fly ash, 60 parts of slag powder, 700 parts of fine aggregate, 1000 parts of pretreated coarse aggregate, 8 parts of water reducing agent, 160 parts of water and 14 parts of aggregate interface reinforcement agent.

[0074] The preparation process of the aggregate interface strengthener is as follows: add 13 parts of ethanol and 7 parts of water into a reactor and stir evenly to form a mixed solvent; under stirring, slowly add 4 parts of aminosilane coupling agent into the mixed solvent and continue stirring for 40 minutes to fully mix and hydrolyze it; gradually add 3 parts of nano-silica into the reactor and continue stirring for 60 minutes to ensure that the nano-silica is evenly dispersed in the solution; ultrasonically disperse for 15 minutes to obtain a uniform and stable aggregate interface strengthener, which is sealed and stored for later use.

[0075] The preparation process of pretreated aggregate is as follows:

[0076] 1) After using a crusher to initially crush the sand and gravel aggregates, the aggregates of different particle size ranges are initially screened and separated;

[0077] 2) Install a stirring device in the water tank or increase the disturbance of the water flow to ensure the uniformity of the aggregate after being rinsed in the flushing tank, and then air-dry;

[0078] 3) Immerse the aggregate in the aggregate interface strengthener for 60 minutes;

[0079] 4) After the aggregate is dried, the required pretreated aggregate is obtained.

[0080] Comparative Example 2

[0081] A high-performance concrete with aggregate interface reinforcement comprises the following components: 330 parts of cement, 70 parts of fly ash, 60 parts of slag powder, 700 parts of fine aggregate, 1000 parts of coarse aggregate without adsorbed interface reinforcement agent, 8 parts of water reducing agent and 160 parts of water.

[0082] The preparation process of pretreated aggregate is as follows:

[0083] 1) After using a crusher to initially crush the sand and gravel aggregates, the aggregates in different particle size ranges are initially screened and separated.

[0084] 2) Install a stirring device in the water tank or increase the disturbance of the water flow to ensure that the aggregate is rinsed evenly through the flushing tank and then air-dried.

[0085] The concrete prepared in the above-mentioned Examples 1-2 and Comparative Examples 1-2 were cured respectively, and the compressive strength test was performed after 28 days, and the compressive strength loss rate test was performed after 300 freeze-thaw cycles. The results are shown in Table 1.

[0086] Table 1 Compressive strength / MPa Compressive strength loss rate / % Example 1 69.2 10.6% Example 2 73.1 8.5% Comparative Example 1 64.5 15.3% Comparative Example 2 60.3 22.4%

[0087] As can be seen from Table 1, the compressive strength of Examples 1-2 is greater than that of Comparative Examples 1-2, and the compressive strength loss rate after 300 freeze-thaw cycles is also less than that of the Comparative Examples;

[0088] The difference between Example 2 and Comparative Example 1 is that the aggregate of Comparative Example 1 is not loaded with the interface strengthener by a vacuum impregnation machine, and the compressive strength of Example 2 is greater than that of Comparative Example 1, and the compressive strength loss rate is less than that of Comparative Example 1, which indicates that the surface of the aggregate can better load the interface strengthener by using the vacuum impregnation method, and fully react with the slurry, thereby ensuring the compactness of the concrete;

[0089] The difference between Example 2 and Comparative Example 2 is that the surface of Comparative Example 2 is not pretreated with an interface strengthener. The compressive strength of Example 2 is greater than that of Comparative Example 2, and the compressive strength loss rate is less than that of Comparative Example 1. This indicates that pretreatment of the aggregate surface with an interface strengthener significantly improves the interface transition zone of the concrete and gives the concrete good mechanical properties.

[0090] A 28-day-old concrete sample with a diameter of about 6 mm was taken at the interface with the aggregate, and a mercury porosimeter was used to test the pore structure. The volume percentage of pores was mainly tested, mainly for pores below 20 nm as harmless pores and pores between 20 and 50 nm as less harmful pores. The results are shown in Table 2 below.

[0091] Table 2 Pores below 20nm / % 20-50nm pores / % Example 1 42% 28% Example 2 48% 27% Comparative Example 1 36% 27% Comparative Example 2 31% 30%

[0092] As can be seen from Table 2, through the pore size classification of Examples 1-2 and Comparative Examples 1-2, it can be seen that the use of an interface strengthener on aggregate can increase the harmless pores of concrete, further reduce the harmful pores, and help reduce the porosity of cement paste and increase the density of the structure;

[0093] Comparison between Example 2 and Comparative Example 1 shows that the use of the impregnation method for aggregates can better bond the aggregates to the concrete interface and reduce the porosity;

[0094] From the comparison between Example 2 and Comparative Example 2, it can be seen that pre-treating the aggregate surface with an interface strengthener can further refine the pores of the concrete.

[0095] The above-mentioned Examples 1-2 and Comparative Examples 1-2 were cured respectively, and the concrete cured for 28 days was tested for its chloride ion penetration resistance according to the standard "Test Method for Long-term Performance and Durability of Ordinary Concrete". The results are shown in Table 3.

[0096] As can be seen from Table 3, through the pore size classification of Examples 1-2 and Comparative Examples 1-2, it can be seen that the electric flux and chloride ion diffusion coefficient of the Examples are both smaller than those of the Comparative Examples;

[0097] Comparing Example 2 with Comparative Example 1, the electric flux of Example 2 was reduced by 36.0%, and the 28d chloride ion diffusion coefficient of the concrete was reduced by 25.5%, which indicates that the porosity of the concrete was reduced by using the impregnation method for the aggregate;

[0098] By comparing Example 2 with Comparative Example 2, it can be seen that the electric flux of Example 2 is reduced by 46.9%, and the 28d chloride ion diffusion coefficient of concrete is reduced by 33.3%. This shows that the use of an interface strengthener on aggregate can reduce the electric flux and chloride ion diffusion coefficient of the concrete anti-chloride ion penetration test, and pre-treating the aggregate surface with an interface strengthener can compact the pores of the concrete and prevent water leakage.

[0099] In summary, the high-performance concrete with aggregate interface reinforcement provided by the present invention has a reasonable combination of material components. By pretreating the aggregate with an interface reinforcement agent, the interface bonding strength can be improved, the pores and microcracks can be reduced, and the mechanical properties and durability of the concrete can be significantly improved.

[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should all be covered by the scope of the technical solution for protection of the present invention.

Claims

1. A high performance concrete with aggregate interface reinforcement, characterized in that: Its composition, by weight, includes the following components: 300-400 parts of cement, 50-100 parts of fly ash, 50-100 parts of slag powder, 600-800 parts of fine aggregate, 1000-1200 parts of pretreated coarse aggregate, 5-10 parts of water reducer, 150-180 parts of water, and 10-20 parts of aggregate interface strengthener; The aggregate interface strengthener comprises a silane coupling agent, nano-silicon dioxide, ethanol and water; the aggregate interface strengthener comprises the following components by weight: 3-5 parts of silane coupling agent, 3-5 parts of nano-silicon dioxide, 10-15 parts of ethanol and 5-10 parts of water; The pre-treated coarse aggregate is 5-25 mm continuously graded crushed stone, the surface of the pre-treated coarse aggregate contains an aggregate interface strengthener, and the mud content of the pre-treated coarse aggregate is not more than 1.0%.

2. The high performance concrete with aggregate interface reinforcement according to claim 1, characterized in that: The fine aggregate is medium sand with a fineness modulus of 2.3-2.8, and the mud content of the fine aggregate is not more than 2.0%.

3. The high performance concrete with aggregate interface reinforcement according to claim 1, characterized in that: The cement is silicate cement or ordinary silicate cement, and the strength grade of the cement is not less than 42.

5.

4. The high performance concrete with aggregate interface reinforcement according to claim 1, characterized in that: The fly ash is Grade I fly ash, and the ignition loss of the fly ash is not more than 5%; the slag powder is Grade S95 slag powder, and the specific surface area of ​​the slag powder is not less than 400m 2 / kg.

5. The high performance concrete with aggregate interface reinforcement according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate of the water reducing agent is not less than 25%.

6. The high performance concrete with aggregate interface reinforcement according to claim 1, characterized in that: The silane coupling agent is one of epoxy silane coupling agents, amino silane coupling agents, and methacrylate silane coupling agents, or a mixture of more than one of these.

7. The high performance concrete with aggregate interface reinforcement according to claim 1, characterized in that: The specific steps of preparing the aggregate interface strengthener are: S1, weighing ethanol and water according to weight components, adding them into a reaction kettle and stirring them evenly to obtain a mixed solvent A; S2, adding a weighed silane coupling agent to the mixed solvent under continuous stirring, and stirring for 30-60 minutes to obtain a mixed solvent B; S3, adding the weighed nano-silicon dioxide into the reaction kettle and stirring for 60-90 minutes to make the nano-silicon dioxide evenly dispersed in the solvent to obtain a mixed solvent C; S4, performing ultrasonic dispersion on the obtained mixed solvent C, the ultrasonic time is 15 minutes, and obtaining an aggregate interface strengthener.

8. The high performance concrete with aggregate interface reinforcement according to claim 1, characterized in that: The specific steps of the coarse aggregate pretreatment are: The first step is to use a crusher to preliminarily crush the sand and gravel aggregates, screen and separate the aggregates in different particle size ranges, and select the aggregates in the particle size range of 5-25mm; The second step is to place the selected aggregate in a flushing tank for flushing, and then air-dry the aggregate after the flushing is completed; The third step is to immerse the air-dried aggregate in the prepared aggregate interface strengthener, and use a vacuum impregnation machine to absorb the aggregate interface strengthener for 30-60 minutes; The fourth step is to dry the aggregate after the vacuum impregnation machine has finished adsorption, thus completing the pretreatment of the coarse aggregate.

9. The high performance concrete with aggregate interface reinforcement according to claim 8, characterized in that: The vacuum impregnation machine is used at an ambient temperature of 20-30° C. and a pressure of 0.6-0.8 MPa.

Citation Information

Patent Citations

  • High-strength recycled aggregate concrete and preparation method thereof

    CN115073097A

  • Machine-made sand concrete and preparation method thereof

    CN115947567A

  • Surface-modified steel fiber, modification method and concrete based on steel fiber

    CN117800641A